2019
DOI: 10.1021/acs.nanolett.9b01241
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Nanoscale Analysis of the Emission from Wurtzite versus Zincblende (In,Ga)As/GaAs Nanowire Core–Shell Quantum Wells

Abstract: arXiv:1903.07372v4 [cond-mat.mes-hall]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Regarding NW structures, morphology, crystal defects and crystal phase can influence the local composition in various material systems. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] For instance, Al tends to accumulate at the vertices of the self-formed, hexagonal shell in AlGaAs NWs due to its different facets. 7 Furthermore, the crystallinity could also impact the compositional distribution of NWs, as several studies found the preferential incorporation of some adatoms at the defect sites often leads to elemental segregation at the vicinity of twins, [11][12][13] which, on the other hand, indicates a means of composition modulation by controlling crystal twinning.…”
mentioning
confidence: 99%
“…Regarding NW structures, morphology, crystal defects and crystal phase can influence the local composition in various material systems. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] For instance, Al tends to accumulate at the vertices of the self-formed, hexagonal shell in AlGaAs NWs due to its different facets. 7 Furthermore, the crystallinity could also impact the compositional distribution of NWs, as several studies found the preferential incorporation of some adatoms at the defect sites often leads to elemental segregation at the vicinity of twins, [11][12][13] which, on the other hand, indicates a means of composition modulation by controlling crystal twinning.…”
mentioning
confidence: 99%
“…The CL map in Figure 3b shows that the high energy emission originates from an approximately 350 nm long segment close to the top of the NWs, that we assign to a wurtzite (WZ) (In,Ga)As coaxial QW segment, as we have recently reported for similar structures without QDs. 21 The formation of a WZ segment on top of zincblende (ZB) GaAs NWs during core growth is related to the consumption of the Ga droplets prior to shell growth. The CL map in Figure 3c shows that the low energy emission originates from spatially localized states distributed along the NWs, consistent with its attribution to QD states.…”
Section: Resultsmentioning
confidence: 99%
“…For all investigated NWs, SEM images and CL hyperspectral line scans were recorded before and after X-ray exposure using a Zeiss Ultra55 field-emission scanning electron microscope operated at an acceleration voltage of 5 kV with beam currents of 0.2-0.3 nA. For low-temperature CL measurements at 15 K, the scanning electron microscope is fitted with a Gatan MonoCL4 system and a He-cooled sample stage (Lä hnemann et al, 2019). To measure the as-grown NWs, the sample is cleaved close to the line of NWs and mounted at an angle of 45 , which is accounted for when plotting the CL.…”
Section: Methodsmentioning
confidence: 99%
“…The WZ polytype is formed in the upper part of the NW (see Fig. S5a in the supporting information) when the Ga droplet is consumed at the end of the core growth (Rieger et al, 2013;Lä hnemann et al, 2019). The WZ Bragg reflection undergoes a rapid thermal lattice expansion before disappearing after 92 min of exposure.…”
Section: Rsms Of the 111 Bragg Reflectionmentioning
confidence: 99%